A study of the Namibian transitional language policy in education and the role of code-switching in achieving it - Kela, Judith Namubi (Linguistics, 2023)
The study investigated the Namibian transitional language in education policy and the role of code-switching in achieving it. Firstly, the study identified the types, structures and roles of code-switching in the Grade 4 bilingual classroom. Secondly, the study established the challenges faced by educators and students regarding English as the medium of instruction during the transition phase. Thirdly, the study established the challenges that educators face in implementing the Namibian language in education policy during the transition phase in Grade 4. The data were collected at the Gabriel Mubita Primary School (pseudonym) of the Zambezi region of Namibia. The study adopted qualitative research methods and data were collected via classroom observations and in-depth interviews. Furthermore, the participants were two educators who were observed and interviewed, together with their Grade 4 students. The data of the study were audio and visual recorded, translated and transcribed. Thereafter, the data collected were linguistically and thematically analysed into themes and sub-themes. The findings of the study were that code-switching was predominately utilised by educators and students at the school under investigation. It was revealed that educators employed three different types of code-switching namely situational, educational and interpersonal codeswitching for pedagogical, teaching and social reasons. The research also found that three different structures of code-switching were utilised by educators, mainly intra-sentential and inter-sentential, while tag-switching was rarely utilised. Code-switching was utilised for roles such as: to encourage students to participate in the classroom, for explanations and clarification purposes, to maintain discipline in the classroom, to show solidarity, to reiterate, to translate and to explain the subject content that students could not grasp as they were beginners. The findings revealed that educators and students faced challenges such as lack of English proficiency, shortage of teaching and scholarship materials, students' linguistic under-preparedness and limited exposure to the target language. Lastly the findings showed that educators had insufficient training on the transition phase, lack of policy awareness, and that the transition to English as the medium of instruction takes place too early. The study recommends that the policymakers must involve educators when developing the policies and ensure that educators are trained in policymaking, orthography of two common languages such as Subiya and Sifwe must be developed since students in the Zambezi Region are not taught in their mother tongue but rather in Silozi, the lingua Franca of the Zambian origin, educators must be given a pre-service and in-service training by the Ministry of Education on how to deal with code-switching or formulate a language policy that includes code-switching since it is considered a powerful teaching tool during the transition phase, teaching and learning material resource shortages within schools should be addressed by the Ministry of Education.